Use of Fermented Black Tea (Camellia sinensis) Factory Wastes in Standard Rat Diets - Buğra Genç; Nilüfer Kuruca; Gül Fatma Yarım; Tolga Güvenç; Emre Özan; Bahadır Müftüoğlu; Tayfun İde; Aşkın Nur Derinöz Erdoğan; Serdar Odacı (Veterinary Sciences)
Although there are studies on the use of different tea extracts in animal diets, there are no studies on the use of fermented black tea factory production waste (FTFW) in rodent diets. This study aims to evaluate the effects of FTFW, considered an environmentally hazardous waste, in standard rat diets regarding nutritional, histopathological, and biochemical parameters. In this study, 40 male Wistar albino rats (70 days old, with a live weight of 200–250 g) were divided into four groups, each containing 10 rats. They were fed standard rat diets for 63 days, with varying amounts (0%, 3%, 5%, and 10%) of tea production waste. At the end of the experiment, biochemical analysis of blood and histopathological analysis of all organs were performed. There was no significant difference between the groups in terms of body weight, internal organ weights, or serum biochemical parameters (p > 0.05). No pathological findings were observed in any of the groups. The group receiving 10% tea waste, which had the highest total polyphenol level (1.42 ppm), also showed the highest serum total antioxidant status (TAS) (p < 0.05). In contrast, this group had the lowest total oxidant status (TOS) and oxidative stress index (OSI) levels (p < 0.05). The study concluded that FTFW can be included in the pellet diet of rats without changing their general health status and that a potential environmental pollutant can be used in rat diets.